Electrochemical Studies on the Redox Behavior of Zr(IV) in the LiCl-KCl Eutectic Molten Salt and Separation of Zr and Hf. Issue 2 (23rd January 2020) - Li, Shaolong; Che, Yusi; Song, Jianxun; Li, Chenyao; Shu, Yongchun; He, Jilin; Yang, Bin
Abstract : Electrochemical behavior of Zr(IV) in LiCl-KCl-ZrCl4 molten salt on molybdenum electrode was systematically studied by a series of electrochemical techniques such as cyclic voltammetry, square wave voltammetry and chronopotentiometry. It was investigated that the Zr(IV) was first reduced to Zr(III) in this system, which is different from most studies in which Zr(IV) is first reduced to Zr(II). The activation energy of Zr(IV) converted to Zr(III) was calculated to be 24.6 kJ mol −1 by measuring the diffusion coefficients of Zr(IV) at 450 °C, 500 °C, and 550 °C. Through research, the nucleation of zirconium belongs to the progressive nucleation on molybdenum electrode in LiCl-KCl-ZrCl4 (0.0359 mol L −1 ) at 500 °C at −3.0 V vs Cl2 /Cl − . Constant current electrolysis (Current density 0.52 A cm −2, duration 500 min) was carried out in LiCl-KCl-ZrCl4 system and the electrolytic product was porous metallic zirconium. More importantly, it is found that the difference in decomposition potential between Zr(II) and Hf(II) is the largest by calculation and test compared with their trivalent and tetravalent states, and they may be separated by electrolysis, which provides a theoretical reference for the electrolytic preparation of nuclear grade zirconium.